2012
DOI: 10.1590/s0047-20852012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Perfil clínico e sociodemográfico de adolescentes que permaneceram e não permaneceram no tratamento em um CAPSad de Cuiabá/MT

Abstract: OBJETIVO: Comparar o perfil clínico e sociodemográfico dos adolescentes que permaneceram e que não permaneceram no tratamento no Centro de Atenção Psicossocial para Álcool e outras Drogas (CAPSad). MÉTODO: Estudo transversal, baseado no registro de prontuários de 125 usuários que estiveram em tratamento no CAPSad Adolescer em Cuiabá/MT, no período de junho de 2009 a junho de 2011. RESULTADOS: A permanência no tratamento foi predominante no sexo masculino, entre usuários que fizeram uso pesado de substâncias ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 17 publications
1
8
0
17
Order By: Relevance
“…Most clinical and medical care variables were common in the articles, regardless of the specialty of the PCC under study; however, we observed some specificities in users of adPCC and caPCC -for example, in studies that had as target population the users of caPPC, these specificities were school report and job situation of the parents (Nascimento et al, 2014); frequency and time of use of psychoactive substance and damages caused by it were added in adPCC, in addition to problems with justice, considering the specificity of each service (Almeira et al, 2014;Araújo et al, 2012;Oliveira et al, 2013;Rodrigues et al, 2013).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Most clinical and medical care variables were common in the articles, regardless of the specialty of the PCC under study; however, we observed some specificities in users of adPCC and caPCC -for example, in studies that had as target population the users of caPPC, these specificities were school report and job situation of the parents (Nascimento et al, 2014); frequency and time of use of psychoactive substance and damages caused by it were added in adPCC, in addition to problems with justice, considering the specificity of each service (Almeira et al, 2014;Araújo et al, 2012;Oliveira et al, 2013;Rodrigues et al, 2013).…”
Section: Resultsmentioning
confidence: 92%
“…These stereotypes determine the expected behaviors and boundaries from the sexes, allowing for men and women to have different experiences, (Almeida et al, 2014) which favors men affected by mental and behavioral disorders from the use of alcohol and drugs and schizophrenia Tarasconi;Scortegagna, 2008). In addition, the low prevalence of female population (especially in adPCCs) can be explained by the discrimination that women addicted to alcohol and/or drugs face besides having to deal with feelings of guilt, shame, fear, and dependence (Araújo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Studies on licit and illicit drug users have reported that the younger the users are, the lower the chances are that they will remain in treatment. 29 The degree of success of and adherence to treatment among young individuals presenting substance abuse depends on variables such as severity of dependence and motivation to change behavior, among other things. These two variables proved to be important in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Estudo 11 realizado com o fim de analisar fatores que influenciam a permanência de adolescentes no tratamento no CAPS identificou que a integração do CAPS aos serviços da rede comunitária constitui uma das variáveis essenciais para a permanência desses usuários no serviço; demonstrando que os adolescentes que não se valeram de qualquer tipo de integração entre os diversos dispositivos da rede permaneceram menos tempo no CAPS, em relação aos usuários que tiveram acesso aos serviços da rede. Ainda conforme o estudo 11 , a maior permanência do usuário de um CAPS integrado à rede comunitária se deve ao reconhecimento desse usuário de que ele faz parte da comunidade, e essa percepção de pertencimento pode estimulá-lo a permanecer em tratamento.…”
Section: Discussão Orientação Das Decisões Judiciais Em Relação à Assunclassified